The aerial survey programme of the Kenya rangeland ecological monitoring unit: 1976-79 - Stelfox, J.G.; Peden, Donald G. (International Livestock Centre for Africa, 1981)
Describes the organization, objectives and results of the aerial survey programme of the Kenyan Rangeland Ecological Monitoring Unit from 1976 to 1979, with particular reference to the methodology used, animal population estimates, esp. herbivores, and reliability of aerial survey data in terms of aerial, ground & remote sensing counts.